SUCCESSFUL SELF-EMPLOYMENT RE-EMPLOYMENT AMONG MIDDLE-AGED AND OLDER ADULTS IN TAIWAN: AN ADULT LEARNING PERSPECTIVE - Lee, Ya-Hui; Cha, Hsien-Ta (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Global aging presents a significant challenge, leading to the rise of the concept of "encore career," where continue working after retirement benefits individuals, families, and society. This study aims to explore the re-employment process of middle-aged and older adults in Taiwan through self-employment. Using qualitative research methods, 33 successfully self-re-employed individuals were interviewed, with an average age of 57.3 and an average self-employment duration of 5.6 years. Findings include: (1) External factors for re-employment include meeting economic needs and ensuring financial security, while intrinsic motivation centers on self-fulfillment; (2) Learning motivation stems from acquiring knowledge and experience in new work; (3) Participants overcame employment challenges through self-empowerment, consulting experts, persistent efforts, and leveraging past experiences and resources; (4) Benefits of re-employment include a sense of achievement, expanded social networks, and enhanced quality of life. These findings provide insight for policymakers and middle-aged or elderly individuals considering self-employment.